2014
DOI: 10.1093/rheumatology/keu332
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate pain relief and large functional loss among patients with knee osteoarthritis: evidence from a prospective multinational longitudinal study of osteoarthritis real-world therapies

Abstract: Objective. To estimate the prevalence of inadequate pain relief (IPR) among patients with symptomatic knee OA prescribed analgesic therapy and to characterize patients with IPR.Methods. Patients ≥50 years old with physician-diagnosed knee OA who had taken topical or oral pain medication for at least 14 days were recruited for this prospective non-interventional study in six European countries. Pain and function were assessed using the Brief Pain Inventory (BPI) and the WOMAC; quality of life (QoL) was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
95
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(104 citation statements)
references
References 33 publications
5
95
0
4
Order By: Relevance
“…However, in its management, inadequate pain relief (IPR) was occurred in 54-64% of patients. Satisfaction and quality of life become worse because of IPR [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in its management, inadequate pain relief (IPR) was occurred in 54-64% of patients. Satisfaction and quality of life become worse because of IPR [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Among the study of OA therapy, non steroidal anti-inflammatory drugs (NSAIDs) are the most widely prescribed medication [6][7][8], but they often cause a dissatisfaction in the treatment of pain [9]. The inability of NSAIDs in overcoming the pain can be caused by the analgesic ceiling effect.…”
Section: Introductionmentioning
confidence: 99%
“…One of the psychological factors assessed by studies in our review was depression. Of eleven studies [14][15][16][17][18][19][20][21][22][23][24], six at least showed a significant relationship between depression and pain, but these findings corresponded to evidence level IV because they were confirmed by cross-sectional studies; the results of the two cohort studies were not consistent. Pain catastrophizing had been measured by ten studies [14,15,19,20,23,[25][26][27][28][29] in our review and was shown to be related with pain worsening in six cross-sectional studies as evidence level IV and in one prospective cohort study as evidence level II.…”
Section: Assessment Of the Risk Of Biasmentioning
confidence: 80%
“…In clinical practice, more often than not, pain relief is inadequate (Conaghan et al, 2014), so people are exposed to possible harms without benefit. In osteoarthritis, some, but not all, people taking standard ibuprofen doses will have adequate pain relief; most of those taking paracetamol will not.…”
Section: Ongoing Use For Chronic Painmentioning
confidence: 99%